ANALISIS KEGAGALAN KEBIJAKAN PEMBANGUNAN MINI ZOO SEBAGAI DESTINASI WISATA EDUKATIF DI KABUPATEN PURWOREJO - Radinka Wastu Amanta; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
The construction of the Mini Zoo tourist attraction in Purworejo Regency, funded by the 2023 Regional Budget (APBD) of Rp 9.4 billion, failed before it was operational due to structural damage. This study analyzes this failure as a public policy failure using Allan McConnell' (2010) logical framework approach and dimensions of failure. The results indicate a chain of failures from the planning stage to implementation. Determining the location in a disaster-prone zone without supporting technical data is a major weakness that impacts construction inconsistencies and the full disbursement of the budget before physical completion. This failure hampered the achievement of Regional Original Income (PAD) targets and undermined public trust. Based on McConnell's (2010) analysis, the failure encompasses process, program, and political dimensions, indicating weak planning and risk management in regional development policies.